2008
DOI: 10.1080/13814780802689154
|View full text |Cite
|
Sign up to set email alerts
|

Management of diabetes in primary care: A structured-care approach

Abstract: Primary-care-led structured care, with relatively limited but well-focused investment, can achieve quality of care for patients with diabetes, comparable to international best practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Those who are not eligible must pay to attend the GP. In terms of diabetes care, at present there are a variety of care arrangements in place across the country including traditional hospital-based management, shared care between general practitioners (GPs) and hospitals, primary care-led management 8 9 and unstructured opportunistic care. The most recent survey of diabetes management in general practice highlighted the lack of formal integration between settings 10.…”
Section: Introductionmentioning
confidence: 99%
“…Those who are not eligible must pay to attend the GP. In terms of diabetes care, at present there are a variety of care arrangements in place across the country including traditional hospital-based management, shared care between general practitioners (GPs) and hospitals, primary care-led management 8 9 and unstructured opportunistic care. The most recent survey of diabetes management in general practice highlighted the lack of formal integration between settings 10.…”
Section: Introductionmentioning
confidence: 99%
“…Treating T2DM in the primary care setting has demonstrated effectiveness comparable to diabetes treatment in a specialist setting, such as endicrinology. 52 Indeed, in a recent study of greater than 17,000 subjects, no difference in glycemic control after insulin initiation was seen between primary versus specialist care. 53 However, the management of patients with diabetes and concomitant mental health conditions in primary care is fragmented, when diabetes is managed by the primary care doctor and mental health interventions are delivered by behavioral health providers (BHPs) outside the primary care office.…”
Section: Introduction Disparitiesmentioning
confidence: 99%
“…51 Another study highlights the complex and reciprocal nature of this relationship, demonstrating that elevated anxiety was associated with subsequent poor self-care, and poor self-care was associated with subsequent elevated anxiety, after controlling for depressive symptoms as a covariate. 52 In summary, several theories attempt to describe the relationship between anxiety and diabetes; some suggest that the emotional impact of a diabetes diagnosis, compounded with the burden of daily diabetes management, can lead to anxiety, while others propose that anxiety leads to, or exacerbates, T2DM through physiological mechanisms. Regardless of the direction or source of the relationship, the literature supports the importance of addressing both conditions simultaneously, as one condition cannot be treated in isolation from the other.…”
Section: Introduction Disparitiesmentioning
confidence: 99%
“…In Spain, for example, primary care centres, which are similar to those participating in the present study, demonstrated significant improvements between 1993 and 2007 in process measures (such as measurement of HbA1c and lipid levels), intermediate outcome measures [including the proportion of patients with HbA1c ≤7.0% (53 mmol/mol), total cholesterol ≤ 200 mg/dl and blood pressure ≤ 140/90 mmHg], and microvascular complications 27, 28. Primary care–led structured care, with relatively limited but well‐focussed investment, can achieve quality of care for patients with diabetes, comparable to international best practice 7. The organisation of primary care service provision for diabetes continues to evolve.…”
Section: Discussionmentioning
confidence: 99%